Upaya Meningkatkan Prestasi Belajar IPA Dengan Metode Pembelajaran Penemuan (Discovery) Pada Siswa Kelas VI SD - sudirman sudirman (Universtas Negeri Makassar, 2021)
The objectives of this action research are: (a) Want to know the increase in student achievement after the implementation of discovery learning. (b) Want to know the effect of students' learning motivation after the implementation of the discovery learning method. This research uses three rounds of action research. Each round consists of four stages, namely: design, activities and observations, reflection, and revision. The target of this study was the sixth grade students of SD Inpres Kapasa Makassar. The data obtained were in the form of formative test results, observation sheets for teaching and learning activities. From the results of the analysis, it was found that student learning achievement has increased from cycle I to cycle III, namely, cycle I (68.18%), cycle II (77.27%), cycle III (86.36%). The conclusion of this study is that the discovery method can have a positive effect on the learning motivation of sixth grade students at SD Inpres Kapasa Makassar, and this learning method can be used as an alternative science learning.